144k views
4 votes
Solve the following system of equations by graphing. y = –1∕2x – 2 y = –3∕2x + 2

Solve the following system of equations by graphing. y = –1∕2x – 2 y = –3∕2x + 2-example-1
User Blindmeis
by
5.3k points

1 Answer

1 vote

We can see the solution in the graph as follows:

Solve the following system of equations by graphing. y = –1∕2x – 2 y = –3∕2x + 2-example-1
User NSZombie
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.